Pembuatan Dan Karakterisasi Ekstrak Kering Daun Jambu Biji (Psidium guajava L.) - Zulharmitta Zulharmitta; Ummil Kasypiah; Harrizul Rivai (STIFARM Padang, 2012)
A study about production and characterization of dried guava leaf extract with the addition of lactose as drying agents has been performed. Dried extract characterization result are: powder, brown color, characteristic odor and taste like plant and somewhat bitter taste. Dry extract was made by adding lactose in ratio of extracts:lactose 2:1; 1:1, and 2 : 3 and the best extract was in ratio 2:1. Levels of water-solube compound the extract 2:1 was 83.90% ± 1.49%, levels of ethanol. Soluble compounds 13.01% ± 0.11%, total flavonoid content of 1.17% ± 0.01%, loss on drying 1.52% ± 0.07%, apparent specific gravity 0.60 g/mL and specific gravity of incompressible 0.78 g/mL, total ash content of 1.174% ± 0.006% and acid insoluble ash content of 0.946% ± 0.036%.